Hubungan Efek Samping Obat Dengan Length Of Stay (LOS) Pasien Jantung Koroner Di Rumah Sakit “X” - Inaratul Rizkhy Hanifah; Asa Puspagiri Setiyasih; Lucia Vita Inandha Dewi (Jurnal Farmasi Indonesia, 2022)
Coronary heart disease (CHD) is caused by the narrowing and blockage of blood vessels that carry blood to the heart. CHD is listed as the highest deadly disease by WHO. CHD treatment is carried out long-term and uses a combination of several drugs, so there is a risk of drug side effects. Length of stay (LOS) is one indicator of successful therapy for CHD patients. However, no correlation studies of LOS with the incidence of drug side effects in CHD patients. Therefore, the purpose of the study was to analyze the potential side effects that occur in CHD therapy and to find the relationship with LOS in the "X" Hospital in Surakarta in 2021. This research uses a descriptive observational method by retrospectively taking patient medical record data that match the inclusion criteria. The sample in this study was 81 patients whose results were tabulated and analyzed univariately by describing the results based on the percentage of events. The reference in this study was Meyler's Side Effects of Drugs guidelines and several supporting journals. To find the relationship between the incidence of drug side effects with LOS using SPSS with the chi-square test. The result show that 23 patients (28%) had the incidence of side effects from CHD treatment. Potential side effects arising in patients include muscle pain; weakness; fever; diarrhea; dizziness; constipation; and nausea-vomiting; are 43.48%, 26.09%, 13.04%, 4.35%, 4.35%, 4.35%, 4.35%, respectively. There was no correlation between side effects and LOS (p=0.803; OR=1,132).